Perceived misinformation, disinformation and malinformation experience and the relationship with information overload - Masrek, Mohamad Noorman; Baharuddin, Mohamad Fazli; Altaf, Asif (Record and Library Journal, 2024)
Background of the study: In today's digitally saturated world, individuals face cognitive overload due to the vast influx of information, including misinformation, disinformation, and malinformation. Purpose: This study investigates the relationships between perceived experiences of misinformation, disinformation, and malinformation, and their impact on information overload among Malaysian students. Method: Data were collected from 352 Malaysian students using a survey method and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). Participants reported their perceptions of misinformation, disinformation, malinformation experiences, and information overload on a Likert scale. Findings: Results indicate that students experience moderate levels of misinformation, disinformation, and information overload, while malinformation was less prominent. Nevertheless, significant positive relationships were found between perceived misinformation, disinformation, and malinformation experiences, and information overload, suggesting that students encountering higher levels of these information types are more likely to experience cognitive overload. Conclusion: This study underscores the challenges students face in processing vast amounts of information. It contributes to the theoretical understanding of how misinformation, disinformation, and malinformation contribute to information overload and emphasizes the need for promoting information literacy and critical thinking to mitigate these effects.